2011
DOI: 10.1111/j.1365-2966.2011.19624.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy pairs in the Sloan Digital Sky Survey - IV. Interactions trigger active galactic nuclei

Abstract: Galaxy-galaxy interactions are predicted to cause gas inflows leading to enhanced nuclear star formation. This prediction is borne out observationally, and is also supported by the gas-phase metallicity dilution in the inner regions of galaxies in close pairs. In this paper we test the further prediction that the gas inflows lead to enhanced accretion on to the central supermassive black hole, triggering activity in the nucleus. Based on a sample of 11 060 Sloan Digital Sky Survey galaxies with a close compani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
425
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(483 citation statements)
references
References 100 publications
48
425
9
1
Order By: Relevance
“…These results are generally consistent with the broader literature, in which a coincidence of AGN and merger activity (at various stages of the merger process) has been reported (e.g. Inskip et al 2010;Koss et al 2010;Schawinski et al 2010;Ellison et al 2011;Carpineti et al 2012). In particular, Pace & Salim (2014) have recently studied the local neigbourhood of radio-loud galaxies in the nearby Universe, finding a clear excess of satellites within 100 kpc, compared to their radio-quiet satellites.…”
Section: T R I G G E R I N G O F L O C a L Ag Nsupporting
confidence: 82%
“…These results are generally consistent with the broader literature, in which a coincidence of AGN and merger activity (at various stages of the merger process) has been reported (e.g. Inskip et al 2010;Koss et al 2010;Schawinski et al 2010;Ellison et al 2011;Carpineti et al 2012). In particular, Pace & Salim (2014) have recently studied the local neigbourhood of radio-loud galaxies in the nearby Universe, finding a clear excess of satellites within 100 kpc, compared to their radio-quiet satellites.…”
Section: T R I G G E R I N G O F L O C a L Ag Nsupporting
confidence: 82%
“…The Soltan argument is consistent with the general picture in which galaxy mergers trigger gas inflow in the nuclear region, feeding quasar activity [25,27,95]. A 10 9 M MBH is thought to have undergone several of such mergers in its lifetime, acquiring most of its mass through relatively short (∼10 7 yrs) Eddington limited accretion episodes.…”
Section: The Making Of the Giants: Massive Black Hole Accretion Historysupporting
confidence: 63%
“…are considered to be sufficient to move some of the available gas to the inner regions of galaxies to feed black holes (e.g. Ellison et al 2011), especially in low accretion systems at low redshifts. Morphological studies of AGN host galaxies indicate that the correlations observed between the properties of black holes and that of their host galaxy are tight for ellipticals and bulge galaxies but not for disk galaxies with pseudo bulges (e.g.…”
Section: Interpretation Of the Correlation Between Sfr And Agn Powermentioning
confidence: 99%